Pengembangan Usaha Kerang Kering sebagai Produk Unggulan Masyarakat di Desa Suka Maju Kabupaten Batubara - Adil Arifin; Indra Fauzan; Suci Rahmadani; Fajar Utama Ritonga (Yayasan Literasi Sains Indonesia, 2024)
Mapping of local economic potential needs to be carried out to determine the potential that exists in the area and the human resources it has. Batu Bara Regency is one of the districts in North Sumatra which has potential in the marine sector, such as fish, shrimp, crab, shellfish, and so on. Various marine-based business activities have great potential to be developed in this region. One form of this business is the dried shellfish business in Suka Maju Village, Batu Bara Regency. This dry shellfish business is carried out by around 12 community groups. However, it is very unfortunate, there are several obstacles faced by the community which are the reason why the dried shellfish business has not developed. Among them is that there is no legal entity that protects the business, so the price is according to the agent's request. Second, there is no product packaging, and the business group's lack of knowledge in product marketing. The results of this service are activities in the form of training on product packaging, product marketing, and managing legal entities for businesses.